Comparison of Pneumatonometry and Transpalpebral Tonometry Measurements of Intraocular Pressure during Scleral Lens Wear. Issue 9 (September 2020) - Fogt, Jennifer Swingle; Nau, Cherie B.; Schornack, Muriel; Shorter, Ellen; Nau, Amy; Harthan, Jennifer S.
ABSTRACT: SIGNIFICANCE: As scleral lens wear becomes more common, understanding the impact of these lenses upon ocular physiology is critically important. Studies on the effect of scleral lens wear upon intraocular pressure (IOP) have used different instruments and have reported conflicting results. PURPOSE: The purpose of this study was to compare assessment of IOP during scleral lens wear using pneumatonometry and transpalpebral tonometry. METHODS: Twenty healthy subjects wore a small-diameter (15.2 mm) and a large-diameter (18.0 mm) scleral lens on the right eye, each for 1 hour in randomized order. IOP was assessed with pneumatonometry and transpalpebral tonometry on both eyes before lens application, immediately after lens application, after 1 hour of lens wear, and immediately after lens removal. Paired t test compared mean IOP in the study eye to the control eye. Repeated-measures ANOVA was performed to take instrumentation, lens diameter, and their interaction into account in an analysis of the change in IOP in the study eye. RESULTS: Mean peripheral IOP measured with pneumatonometry was not significantly different from baseline at any subsequent measurement. Measurements with transpalpebral tonometry, however, were significantly different during scleral lens wear immediately after application and after 1 hour of wear with both diameter lenses ( P < .005), but were not significantly different after either sized lens was removed. Repeated-measures ANOVA revealed that the instrument used to measure IOP was a significant factor in IOP changes found during lens wear ( P ⩽ .001). CONCLUSIONS: Assessment of IOP during scleral lens wear varies based upon the instrument that is used. Although further studies are clearly needed to further elucidate this issue, clinicians should continue to monitor optic nerve structure and function in scleral lens wearers, as they do in all patients.